2021
DOI: 10.1681/asn.2021010104
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Vaccine Acceptability in Patients on Hemodialysis: A Nationwide Survey

Abstract: BackgroundPatients on dialysis are at increased risk for COVID-19–related complications. However, a substantial fraction of patients on dialysis belong to groups more likely to be hesitant about vaccination.MethodsWith the goal of identifying strategies to increase COVID-19 vaccine uptake among patients on hemodialysis, we conducted a nationwide vaccine acceptability survey, partnering with a dialysis network to distribute an anonymized English and Spanish language online survey in 150 randomly selected facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 15 publications
9
49
2
1
Order By: Relevance
“…Patients that refused vaccine during the initial mobile vaccination clinics were more likely to be younger, female, and lack evidence of prior influenza vaccination. These findings are consistent with prior studies in the general public and dialysis patients (5,6,7). We hypothesized that prior infection with SARS-CoV-2 would reduce vaccine acceptance based on patient belief in natural immunity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients that refused vaccine during the initial mobile vaccination clinics were more likely to be younger, female, and lack evidence of prior influenza vaccination. These findings are consistent with prior studies in the general public and dialysis patients (5,6,7). We hypothesized that prior infection with SARS-CoV-2 would reduce vaccine acceptance based on patient belief in natural immunity.…”
Section: Discussionsupporting
confidence: 93%
“…In these studies, various factors were found to be associated with vaccine hesitancy including: younger age, African American race, lower attained education level and lower influenza vaccination rates (5). A more recent national survey of dialysis patients suggested vaccine acceptance rates could reach as high as 81% under ideal conditions (7). In that survey, similar factors were associated with vaccine hesitancy in the dialysis population as seen in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…In a nationwide vaccine acceptability survey performed in 150 dialysis units in the United States a significant proportion of hemodialyzed (HD) patients hesitate to vaccinate against COVID-19 for fear of potential side effects. Hesitancy among people overall may have recently increased, at least for the short term, because of concerns over rare thrombotic events among people who receive certain types of COVID-19 vaccine [ 3 , 4 ]. BNT162b2 mRNA vaccine against SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) approved for use in the US and Europe was shown to have a favorable safety profile, and its reactogenicity was generally mild or moderate [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, hundreds of articles in worldwide journals have been published using this methodology [7][8][9][10][11]. Moreover, with the COVID-19 pandemic, researchers have been using online questionnaires even more frequently due to contact restrictions, lack of face-to-face contact and no possibility to travel [12][13][14][15][16][17][18]. A similar methodology was employed by Machida et al [19] in their paper about the incorrect use of face masks during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%